Remote concussion history does not affect visually-guided reaching in young adult females - Christopher Fueger; Lauren E Sergio; Sabine Heuer; Labina Petrovska; Wendy E Huddleston (Concussion)
Aim: We examined the long-term effects of concussions in young adult females on visuomotor behavior during a visually-guided reaching task of various complexities. Materials & methods: 20 females w...